2013
DOI: 10.1007/s10802-013-9804-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Problems on the Teacher’s Report Form: A Cross-National, Cross-Clinic Comparative Analysis of Gender Dysphoric Children and Adolescents

Abstract: For gender dysphoric children and adolescents, the school environment may be challenging due to peer social ostracism and rejection. To date, information on the psychological functioning and the quality of peer relations in gender dysphoric children and adolescents has been studied via parental report, peer sociometric methods, and social interactions in laboratory play groups. The present study was the first cross-national investigation that assessed behavior and emotional problems and the quality of peer rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 38 publications
9
69
1
1
Order By: Relevance
“…The results are also in line with previous evidence that indicates a higher proportion of nonconforming gender expression in natal girls diagnosed with a GIDC compared to natal boys diagnosed with a GIDC (e.g. Kane, 2006;Steensma et al, 2013;Wallien et al, 2010). A stronger refusal and social judgment of nonconforming gender expression was reported for boys (Blakemore, 2003;Cohen-Kettenis, et al, 2003).…”
Section: Differences In Play Behavior and Peer Preferences Between Ftsupporting
confidence: 90%
See 2 more Smart Citations
“…The results are also in line with previous evidence that indicates a higher proportion of nonconforming gender expression in natal girls diagnosed with a GIDC compared to natal boys diagnosed with a GIDC (e.g. Kane, 2006;Steensma et al, 2013;Wallien et al, 2010). A stronger refusal and social judgment of nonconforming gender expression was reported for boys (Blakemore, 2003;Cohen-Kettenis, et al, 2003).…”
Section: Differences In Play Behavior and Peer Preferences Between Ftsupporting
confidence: 90%
“…In a sociometric study with n D 28 children who have been referred to a gender clinic in the Netherlands, Wallien, Veenstra, Kreukels, and Cohen-Kettenis (2010) found that, compared to their classmates (n D 495), gender-nonconforming boys experienced more negative social consequences than gender-nonconforming girls did. In a recent cross-national, cross-clinic comparative analysis of gender dysphoric children and adolescents (n D 554 children, n D 174 adolescents), Steensma et al (2013) investigated behavioral and emotional problems and the quality of peer relations assessed with the Teacher's Report Form in a sample of n D 728 gender dysphoric patients (554 children, 174 adolescence; n D 219 natal girls, n D 509 natal boys) who were referred to specialized gender identity clinics in the Netherlands and Canada. Gender dysphoric natal boys had poorer peer relations than gender dysphoric natal girls.…”
Section: Gender Nonconformity and Diagnoses Related To Gender Identitmentioning
confidence: 99%
See 1 more Smart Citation
“…They found a predominance of internalising problems over externalising problems. On average, emotional and behavioural problems in the clinical range were more prevalent in Canada compared to The Netherlands [11, 17, 18]. …”
Section: Introductionmentioning
confidence: 99%
“…In puberty, the development of the body in an undesired direction is generally distressful. Being a victim of bullying and stigmatization as a consequence of rigid and stereotyped gender norms can have a strong negative effect on the psychological health and quality of life of an adolescent with GD [1]. And, in addition, interventions that can be provided by a (mental) health professional to reduce GD (e.g., hormone therapy) are generally efficient but may have iatrogenic side effects.…”
Section: Commentarymentioning
confidence: 99%